Non-alcoholic and alcoholic Fatty Liver Disease - two Diseases of Affluence associated with the Metabolic Syndrome and Type 2 Diabetes: the FIN-D2D Survey - Kotronen, Anna; Yki-Järvinen, Hannele; Männistö, Satu; Saarikoski, Liisa; Korpi-Hyövälti, Eeva; Oksa, Heikki; Saltevo, Juha; Saaristo, Timo; Sundvall, Jouko; Tuomilehto, Jaakko; Peltonen, Markku (BMC public health, 2010)
Background Non-alcoholic fatty liver disease (NAFLD) is known to be associated with the metabolic syndrome (MetS) and abnormal glucose tolerance. Whether alcoholic fatty liver disease (AFLD) is associated with similar metabolic abnormalities has not been examined in a population-based study. We aimed at assessing the prevalences of NAFLD and AFLD, and to examine to what extent these conditions are associated with MetS and abnormal glucose tolerance. Methods The cohort included 2766 Finnish subjects (45-74 years) from the population-based FIN-D2D survey. Features of insulin resistance, components of the MetS, glucose tolerance status by oral glucose tolerance test, serum liver enzyme concentrations, and daily alcohol consumption were assessed. Results Subjects with NAFLD and AFLD were equally obese and had similar fasting and insulin concentrations. The prevalences of NAFLD and AFLD were 21% (95% CI: 19%-22%) and 7% (95% CI: 6%-8%). The MetS was slightly more prevalent in AFLD (73%) than in NAFLD (70%, p = 0.028), and type 2 diabetes was similarly prevalent in NAFLD and AFLD (24-25%). The MetS and type 2 diabetes were more prevalent in subjects with NAFLD or AFLD compared to subjects with normal LFTs (53% and 14%, p < 0.0001 for both). Discussion and conclusion In Finnish middle-aged population, the prevalence of NAFLD is 3-fold higher than that of AFLD. The prevalences of MetS and type 2 diabetes are, however, significantly increased in both NAFLD and AFLD compared to subjects with normal LFTs. Subjects with AFLD are thus similarly metabolically unhealthy as subjects with NAFLD.